2020
DOI: 10.3390/healthcare8040487
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Application of Temporal Self-Regulation Theory to Understand Adherence to Simple and Complex Medication Regimens

Abstract: Medication adherence is a global health concern, and variables of temporal self-regulation theory (TST) have been shown to be important in improving adherence. This qualitative study aims to explore how TST can help explain medication adherence in people’s daily lives, and whether there are differences in the adherence to simple and complex medication regimens. Twenty-nine participants from Australia engaged in semi-structured interviews based on TST (intention, behavioural prepotency, self-regulation), and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Possibly for patients with more complex asthma therapeutic plans and those taking medication for other conditions, the app was perceived as more useful, as they could use the app to better manage treatment adherence. This observation links with a qualitative study that showed that having a consistent routine and planning was considered more relevant by patients with more complex regimens rather than by those with simpler regimens (29). Regarding adherence, a previous study also showed that patients with the highest adherence at baseline were the ones using more frequently an app to improve adherence (21).…”
Section: Discussionsupporting
confidence: 62%
“…Possibly for patients with more complex asthma therapeutic plans and those taking medication for other conditions, the app was perceived as more useful, as they could use the app to better manage treatment adherence. This observation links with a qualitative study that showed that having a consistent routine and planning was considered more relevant by patients with more complex regimens rather than by those with simpler regimens (29). Regarding adherence, a previous study also showed that patients with the highest adherence at baseline were the ones using more frequently an app to improve adherence (21).…”
Section: Discussionsupporting
confidence: 62%
“…Temporal and spatial reminders—whether these involve alarms, memo boards, spreading medication around homes in strategic locations or taking medication at meals or coffee breaks—are a means of incorporating medication into OAs’ daily routines or that of their dyad with their ICs. The emphasis on medication routines has been noted in situations of complex medication regimens [ 53 ]. The integration of medication intake into daily routines and activities is especially observable among polymedicated OAs because they are retired and more likely to be sedentary [ 54 ], and other researchers have concluded similarly [ 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, 'real-world' behavioral demands also vary in their complexity and have been differentially linked to behavior change success. Individuals being prescribed a more complex medication regimen for the first time, for example, have greater difficulties if they have pre-existing executive function weaknesses (Liddelow et al, 2020).…”
Section: Contextual Specificity: How Self-regulation Links Emotion An...mentioning
confidence: 99%